2011
DOI: 10.1093/ageing/afr022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Parkinson's disease as a comorbid diagnosis

Abstract: Clinicians, departments and trusts are compared using Hospital Standardised Mortality Ratios. The benchmarking process makes corrections for patients' past medical histories, using a tool called the Charlson Index of Co-morbidity. Patients with any of 17 conditions receive an adjustment to their expected mortality and length of stay. Although the weighting of these conditions has been altered to take account of advances in medical practice, there have been no conditions added to the list since Charlson's origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This could be explained by a lower sensitivity in Parkinson's disease patients for the CCI in comparison with the CPS. 26 Even if we demonstrated that CPS could be used as a determinant risk factor, we still observed a low median CPS of 11. Thus, we think that more accurate comorbidity scores should be validated to characterize this particular population.…”
Section: Discussionmentioning
confidence: 72%
“…This could be explained by a lower sensitivity in Parkinson's disease patients for the CCI in comparison with the CPS. 26 Even if we demonstrated that CPS could be used as a determinant risk factor, we still observed a low median CPS of 11. Thus, we think that more accurate comorbidity scores should be validated to characterize this particular population.…”
Section: Discussionmentioning
confidence: 72%
“…The impact of Parkinson´s disease (as a comorbid diagnosis) on the burden of hospitalization due to other causes has led to much discussion about recommending its inclusion in a reviewed Charlson Comorbidity Index [ 7 ]. Due to the aging population, the incidence and prevalence of degenerative conditions, such as PD, have increased in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed using the CCI, without being statistically significant. This could be explained by a lower sensitivity in Parkinson’s disease patients for the CCI in comparison with the CPS 26 . Even if we demonstrated that CPS could be used as a determinant risk factor, we still observed a low median CPS of 11.…”
Section: Discussionmentioning
confidence: 57%